The Importance of Working with Didactic Games in Preparatory Children's Independent Thinking and Speech - Isakulova Bakhtigul Khujamovna (Genius Journals, 2022)
The game is the leading type of activity, and the game activity is the most interesting activity accessible to the child. It is through the game joint activity of children and the teacher that it is possible to expand and activate the vocabulary of children, to form the grammatical structure of speech.
Keywords: didactic games; speech development; training; conduct; analysis